Pembelajaran Puisi Berbasis Culturally Responsive Teaching: Studi Kualitatif tentang Respons Peserta Didik - Hanim, Farida; Werdiningsih, Dyah; Badrih, Moh. (Jurnal Ragam Pengabdian, 2026)
This study aimed to develop a poetry teaching module based on the Culturally Responsive Teaching (CRT) approach, determine its validity, and evaluate its effectiveness in improving the literary appreciation of eighth-grade students at SMPN 1 Bangsal. The research employed the Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through observations, interviews, validation questionnaires, documentation, and student achievement tests. The research involved media experts, subject matter experts, learning experts, and eighth-grade students. The analysis revealed that existing poetry instruction lacked connections to students’ cultural experiences and appropriate CRT-based teaching materials. Consequently, a web-based digital poetry module integrating literary appreciation with local cultural contexts was developed. Validation results demonstrated excellent quality, with media experts awarding 93.75%, subject matter experts 91.67%, and learning experts 92.31%, indicating that the module was highly valid and suitable for classroom implementation. Revisions were made based on expert recommendations regarding layout, language, learning outcomes alignment, and local cultural integration. Effectiveness testing produced an average N-Gain score of 0.8271, classified as high, indicating significant improvement in students’ abilities to understand, interpret, appreciate, and respond to literary works. Therefore, the developed CRT-based poetry module is valid, feasible, and effective for classroom learning